Family caregivers’ perceptions and challenges in the care of pressure injuries in daily life: a qualitative study - Yi Chen; Tingting Cai; Ping Le; Lijuan Zhang; Yunxia Chen; Linzhu Wu; Kejian Chen; Changrong Yuan; Yan Lu (BMC Geriatrics)
Abstract Background Pressure injuries are common in home care settings and can severely impact older adults’ quality of life. Family caregivers play a vital role in managing these injuries, yet their limited knowledge and skills may lead to delayed treatment and worsened outcomes. This qualitative study explores family caregivers’ perceptions and challenges in managing initial pressure injuries during daily caregiving. It examines discrepancies between actual caregiving practices and guideline-recommended prevention and treatment strategies. Methods From June to December 2023, 17 older patients with pressure injuries were observed and 17 family caregivers were recruited. A qualitative design combining participant observation and in-depth interviews was employed. Field notes and interview data were analyzed using a three-level coding approach. Qualitative data analysis was performed in NVivo 14 using an inductive thematic analysis method. Results Eight key themes emerged from the analysis. Four themes related to caregiving practices: (1) food preparation and feeding assistance, (2) hygiene maintenance, (3) repositioning and use of supportive devices, and (4) medication and dressing application. Two themes reflected caregivers’ perceptions: (1) a sense of duty and compensatory companionship, and (2) feelings of grief and helplessness. The remaining two themes highlighted major challenges: (1) identifying and responding to early signs of pressure injury, and (2) limited access to professional care and counseling resources. Conclusion This study examined the real-world practices of family caregivers in managing initial pressure injuries, revealing both alignment with and divergence from clinical guidelines. While caregivers actively engage in core caregiving tasks, inconsistencies arise due to limited knowledge, emotional burden, and inadequate resources. A strong sense of responsibility—often accompanied by grief and helplessness—shapes their decisions and actions. Notably, caregivers frequently struggle to recognize early warning signs of deterioration, leading to missed opportunities for timely intervention. These findings highlight key discrepancies between actual care and clinical expectations. To bridge this gap, it is essential to enhance caregiver education, improve access to professional support, optimize the home care environment, and implement comprehensive, multi-level support systems.